2003
DOI: 10.1029/2002jb002117
|View full text |Cite
|
Sign up to set email alerts
|

Percolation conditions in binary fractal fracture networks: Applications to rock fractures and active and seismogenic faults

Abstract: [1] The fracture network patterns in crystalline rock are treated using a binary fractal model described by three fractal geometric parameters: the fractal dimension D of the spatial distribution of fractures, the fractal dimension a of the fracture length distribution, and the maximum fracture length (l max ) normalized by the domain length (L), l max /L. We present a percolation threshold relationship describing the boundary between percolating and nonpercolating conditions in random binary fractal fracture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…A cumulative analysis was executed in order to evaluate the growth of the fault network pattern (i.e., the fault formation process) from the behavior of fractal dimensions D 2 and a on the basis of the binary fractal fracture network (BFFN) model [ Nakaya et al , 2003] and another fracture network model similar to BFFN [e.g., Darcel et al , 2003]. Darcel et al [2003] and Nakaya et al [2003] have reported that a fractal‐based fracture network model such as BFFN can describe the geometry and connectivity of fracture network patterns using two kinds of fractal parameters for the size distribution and the spatial distribution of rock fractures and active and seismogenic faults. The four fundamental modes (M1, M2, M3 and M4; Figure 9) of the relationship between D 2 and a are explained as follows under the condition that the number of fractures increases and the fracture network size expands with time.…”
Section: Resultsmentioning
confidence: 99%
“…A cumulative analysis was executed in order to evaluate the growth of the fault network pattern (i.e., the fault formation process) from the behavior of fractal dimensions D 2 and a on the basis of the binary fractal fracture network (BFFN) model [ Nakaya et al , 2003] and another fracture network model similar to BFFN [e.g., Darcel et al , 2003]. Darcel et al [2003] and Nakaya et al [2003] have reported that a fractal‐based fracture network model such as BFFN can describe the geometry and connectivity of fracture network patterns using two kinds of fractal parameters for the size distribution and the spatial distribution of rock fractures and active and seismogenic faults. The four fundamental modes (M1, M2, M3 and M4; Figure 9) of the relationship between D 2 and a are explained as follows under the condition that the number of fractures increases and the fracture network size expands with time.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for generating a two‐dimensional RBFFN model (2D‐RBFFN) has been reported previously [e.g., Darcel et al , 2003; Nakaya et al , 2003]. In the present study, we develop a 3D‐RBFFN model based on the 2D‐RBFFN model.…”
Section: Methodsmentioning
confidence: 99%
“…For example, fracture connectivity determines the pathway of fluid flow in a fracture network system. On the basis of evidence presented in many previous studies, it is natural to assume that properties of fracture geometry such as size distribution, spatial distribution, and the distributions of aperture, throw, and spacing must be fractal or partial fractal [e.g., Okubo and Aki , 1987; Hirata et al , 1987; Hirata , 1989; Ohno and Kojima , 1992; Marrett and Allmendinger , 1992; Gillespie et al , 1993; Bloomfield , 1996; Cladouhos and Marrett , 1996; Odling , 1997; Bour and Davy , 1997; Van Dijk et al , 2000; Gillespie et al , 2001; Wilson , 2001; Nakaya et al , 2003]. Many phenomena in geology and geophysics, such as fault systems and seismic activity, behave as fractals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations